Synthesis of 2-oxoamides based on sulfonamide analogs of gamma-amino acids and their activity on phospholipase A2 - Antonopoulou, G.; Magrioti, V.; Stephens, D.; Constantinou-Kokotou, V.; Dennis, E. A.; Kokotos, G. (Journal of Peptide Science, 2008)
A variety of lipophilic 2-oxoamides containing sulfonamide analogs of γ-amino acids as well as acyl sulfonamides of γ-aminobutyric acid were synthesized. Their ability to inhibit intracellular GIVA cPLA2 and GVIA iPLA2 as well as secreted GV sPLA2 was evaluated. The sulfonamide group seems a bioisosteric group suitable to replace the carboxyl group in 2-oxoamide inhibitors of GVIA cPLA2.
Keywords: 2-Oxoamides; acyl sulfonamides; aldol reactions; arachidonic-acid; Cells; group-iia; group-iva; group-v; Inhibitors; one-pot conversion; phospholipase a(2); release; sulfonamides; superfamily